English Loanword in Rantau Panjang Language - Maisarah, Ira; Harahap, Alamsyah (Lingual Journal of Language and Culture, 2024)
This research is crucial to understand the connection between language and past communities' cultures. This research used a qualitative approach based on descriptive methods. The researcher employed an unstructured interview as the instrument for gathering data. In this interview, the researcher selected key informants who were both native residents and the older generation in the Rantau Panjang area. The interview results indicated that people in Rantau Panjang have been using English loanwords for several years. Historically, English loanwords were utilised for communication and trading purposes.